SCIENTIFIC FINDINGS ON DATA TRANSMISSION AND RECEPTION THROUGH THE DEVELOPMENT OF A V2X PROTOCOL FOR MULTI-NETWORK URBAN TRANSPORTATION (Modern education and development, 2024)
This article focuses on the development of a new V2X (Vehicle-to-Everything) protocol designed for multi-network urban transportation. V2X communication offers significant opportunities to enhance safety, improve traffic management, and reduce congestion in urban transportation systems. However, existing protocols face limitations in terms of latency, data transmission efficiency, and compatibility across different vehicles. This article employs mathematical models, including channel capacity and throughput calculations, a delay model, and error detection and correction mechanisms, to develop the new V2X protocol. The research results demonstrate that the new protocol ensures high throughput, low latency, and reliable security, making it highly effective for application in multi-network urban transportation systems.